Comparative analysis of Black-Scholes and GARCH models using collar strategy for hedging in telecommunication industry (Telkom, Xl, Indosat) - Soma, Abdul Mukti; Sitepu, Victor Bastanta (International Journal of Accounting and Management Information Systems, 2025)
Purpose: This study examines the implementation of option contracts in the Black-Scholes model by comparing historical volatility and GARCH volatility using a collar strategy on TLKM, EXCL, and ISAT shares for the 2007–2024 period, aiming to determine the most appropriate model under crisis and normal conditions. Research/methodology: The Black-Scholes model is applied with two volatility estimation methods historical and GARCH on options with 1-month and 3-month maturities, analyzed across crisis and non-crisis periods. Results: For TLKM, with a 1-month maturity, GARCH outperformed historical volatility except during the 2008–2009 crisis; for 3 months, historical volatility outperformed in 2007, 2008–2009, and 2023–2024. For EXCL, historical volatility outperformed at 3 months in all conditions and at 1 month during crises; GARCH outperformed at 1 month in non-crisis periods. For ISAT, GARCH outperformed at 1 month except during the 2008–2009 crisis; historical volatility outperformed at 3 months during the non-crisis periods of 2007, 2023–2024, and the 2008–2009 crisis. Conclusions: Performance varies by volatility method, maturity, and market condition. GARCH tends to perform better for short-term maturities in non-crisis periods, while historical volatility performs better for longer maturities and certain crisis periods. Limitations: This study is limited to TLKM, EXCL, and ISAT stocks from 2007–2024, using only Black-Scholes and GARCH models with collar strategy, and may not generalize to other sectors or instruments. Contribution: The study offers empirical evidence on optimal volatility modeling for hedging in Indonesia’s telecommunications sector.